Sustainability, Innovation, and Entrepreneurship: A Research with Administration and Secretariat Students - Paiva, Luis Eduardo Brandão; Lima, Tereza Cristina Batista de; Sousa, Evangelina da Silva; Pontes, Emiliano Sousa (Revista de Negócios, 2019)
This study analyzes the influence of sustainable and innovative behavioral constructs on the entrepreneurial intentions of university students. The investigated students were from the Administration and Executive Secretariat undergraduate programs. The influence on entrepreneurial intention by other entrepreneurs in the family or due to gender was also investigated. This is a descriptive research project of a quantitative nature. A sample of 429 students from a public university was obtained, in which 285 students were from the Administration program and 144 students were from the Executive Secretariat program. Various data analysis techniques were used for the treatment of data, including factorial analysis and logistic regression. The results indicated that sustainable and innovative behaviors influence the entrepreneurial intention of students in both the Administration and Executive Secretariat programs. In addition, entrepreneurs in the family strongly influenced the entrepreneurial intention of these individuals. There was also a gender influence on the entrepreneurial intention: for students from the Administration program, men appeared to be more prone to entrepreneurship than women, but this was not present among Executive Secretariat students. This study also contributes to the promotion of policies and practices at Higher Education Institutions (HEIs), because entrepreneurial intention is at present relevant. It is expected that HEIs incorporate sustainable and innovative social studies and practices to foster social and environmental benefits aligned with entrepreneurship.